The Role of Supervision in Effort To Increase Quality of School Education - Astari, Sharli Yunita (PPSDP International Journal of Education, 2024)
Objective study this will heighten quality learning and create situational learning that will become inspirational, interactive, and pleasant to learn. So that educator must be able to use techniques, methods, strategies, and approaches to learning. Suite something planning supervision academic, prove that 1) have objective supervision; 2) identify; 3) establish as well as design; 4) identify as well as decide source power; 5) compose; 6) arrange procedures as well as monitoring procedures as well as assessment; 7) determine as well as decide steps. For raising quality education, role supervision education cannot be ignored. Supervisor (supervisor, head school) is mandatory to have expertise as well as seriousness in supervising educational forums in order to raise quality education.